Sexual Consent and Epistemic Partiality in Rape Fact-Finding - Talita Ferrantelli (Revista Brasileira de Direito Processual Penal, 2023)
Feminist legal theory has contested rape laws and notions of sexual consent to better reflect the experiences of survivors and address power distortions in legal frameworks that perpetuate women’s subordination. In this paper, I explore an alternative form of criticism to consent-based rape laws and biases within legal systems. I argue that the justifications that are used to select and weigh evidence in rape cases are epistemically suspect because of the unreliability of their epistemic sources. My argument, building on radical realist social analysis in political theory, aims to unveil an epistemic defect in rape evidentiary procedures, which I call epistemic partiality. I suggest that this epistemic defect brings salient reasons to challenge rape laws based on ideals of consent. I hope to show that a radical realist approach may bring reasons to challenge rape laws and flaws in evidentiary systems without the need to centrally agree with or rely on feminist commitments and political goals. This type of criticism may effectively bypass certain limitations of feminist theory and potentially add to discussions focused on power distortions within legal systems.